PERUBAHAN MORFOLOGI STRUKTUR MIKRO PADUAN Cu-Zn 70/30 YANG DILAKUKAN TMCP DI SUHU 300°C - Eka Febriyanti; Amin Suhadi; Ayu Rizeki Ridhowati; Rini Riastuti (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2017)
Cu-Zn 70/30 alloy are used for various equipment to industry application. However, Cu-Zn 70/30 alloy has a weakness that is susceptible corrosion due to exposure to corrosive environments such as chloride ion (Cl-). Therefore, these characteristics can reduce working efficiency and performance equipment. This research focuses to study about increasing of toughness, corrosion resistance, and surface quality from Cu-Zn 70/30 alloy by conducting Themomechanical Control Process (TMCP). Warm rolling on temperature 300°C is experienced by double pass reversible method with deformation 2x25%, 2x30%, and 2x35%. Warm temperature is temperature between hot and cold work for obtain small grains with a narrow grain boundaries. The result showed that as the increase of deformation degree from 31.6% to be 48.93% causes a decrease diameter grain size, the size of the average grain size decrease from 50.53 μm to be 24.41 μm. This phenomenon is due to partial recrystallization which is indicated by existence of nuclei.